Real-time Speed Control of Slider -Crank Mechanism to Perform Punching Operation with Fuzzy Logic Controller - Muhammet, Aydin (Chinese Soc Mechanical Engineers, 2024)
To accomplish the punching procedure on fabric items, a unique slider-crank mechanism was created as part of this study. A DC motor was used to move the input limb or crank. This allowed for the realization of rotational movement in the mechanism's input and the provision of motion transmission to the connecting rod. The piston placed at the connecting rod's output enabled translational movement. Rotational motion is consequently changed into translational motion. The device for punching fabric was mounted with a separate portion that was created for the piston's end. This led to the development of a new slider-crank system for the textile sector. The developed slider-crank mechanism is unique for the textile industry application. Real-time speed control of the crank using a fuzzy logic control was used in this work to achieve the speed control of the mechanism. Additionally, unlike the cards described in the literature, this V-Daq card was used to control the slider-crank mechanism for the first time. As a result, a different slider-crank mechanism has been created that permits automatic punching of multifold fabrics.
Keywords: Slider-crank mechanism; V-daq card; Punching operation; Fuzzy logic controller.